Integrating Protein Engineering and Bioorthogonal Click Conjugation for Extracellular Vesicle Modulation and Intracellular Delivery - Wang, Ming; Altinoglu, Sarah; Takeda, Yuji S.; Xu, Qiaobing (PloS one, 2015)
Exosomes are small, cell-secreted vesicles that transfer proteins and genetic information between cells. This intercellular transmission regulates many physiological and pathological processes. Therefore, exosomes have emerged as novel biomarkers for disease diagnosis and as nanocarriers for drug delivery. Here, we report an easy-to-adapt and highly versatile methodology to modulate exosome composition and conjugate exosomes for intracellular delivery. Our strategy combines the metabolic labeling of newly synthesized proteins or glycan/glycoproteins of exosome-secreting cells with active azides and bioorthogonal click conjugation to modify and functionalize the exosomes. The azide-integrated can be conjugated to a variety of small molecules and proteins and can efficiently deliver conjugates into cells. The metabolic engineering of exosomes diversifies the chemistry of exosomes and expands the functions that can be introduced into exosomes, providing novel, powerful tools to study the roles of exosomes in biology and expand the biomedical potential of exosomes.